Method of functional evaluation of adaptation of volleyball players in microcycles of sports training - Lutkov, V. F.; Miller, L. L.; Smirnov, G. I.; Shadrin, D. I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to substantiate the use of the method of variational pulsometry and electrocardiographic active orthotic test for individual assessment of the adaptation of highly qualified female volleyball players in training microcycles.